2015
DOI: 10.1177/1087057114555307
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Based Screening Assays for the NAD+-Dependent Histone Deacetylase smSirt2 from Schistosoma mansoni

Abstract: Sirtuins are NAD + -dependent histone deacetylases (HDACs) that cleave off acetyl but also other acyl groups from the ε-amino group of lysines in histones and other substrate proteins. Five sirtuin isoforms are encoded in the genome of the parasitic pathogen Schistosoma mansoni. During its life cycle, S. mansoni undergoes drastic changes in phenotype that are associated with epigenetic modifications. Previous work showed strong effects of hSirt2 inhibitors on both worm life span and reproduction. Thus, we post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 33 publications
2
55
0
Order By: Relevance
“…During its life cycle, S . mansoni undergoes drastic changes in phenotype that are associated with epigenetic modifications, including the effects of hSirt2 inhibitors, recently considered a new antiparasite target [ 63 ]. On this basis, a Schistosome Epigenetics Consortium (targets, regulation, and new drugs) was launched to study the potential utility of HDACs in the treatment of adult schistosomiasis and to develop alternate treatments for prazinquantel-resistant Schistosoma.…”
Section: The Epigenetic Landscape In S mentioning
confidence: 99%
“…During its life cycle, S . mansoni undergoes drastic changes in phenotype that are associated with epigenetic modifications, including the effects of hSirt2 inhibitors, recently considered a new antiparasite target [ 63 ]. On this basis, a Schistosome Epigenetics Consortium (targets, regulation, and new drugs) was launched to study the potential utility of HDACs in the treatment of adult schistosomiasis and to develop alternate treatments for prazinquantel-resistant Schistosoma.…”
Section: The Epigenetic Landscape In S mentioning
confidence: 99%
“…) was reported as a weakly selective Sirt1 inhibitor with an IC 50 value in the low micromolar range . In a focused library screening MS3 was also identified as an inhibitor of the schistosomal lysine deacylase smSirt2 in vitro . Moreover, Maurer et al.…”
Section: Small‐molecule Inhibitors Of Sirtuinsmentioning
confidence: 99%
“…This result suggests that inhibition of Smp14 expression targeting SmGCN5 and/or SmCBP1 represents a novel and effective strategy to control S. mansoni egg development and that HATs can be used as a drug target against schistosomiasis. Regarding HDAC, the NAD + -dependent HDAC, smSirt2 in S. mansoni was identified using fluorescence-based screening assays (Schiedel et al, 2015). The class I HDAC s, SmHDAC1, 3, and 8, were identified in S. mansoni (Oger et al, 2008; Marek et al, 2013; Singh and Pandey, 2015).…”
Section: Epigenetic Studies In Schistosomes: What Is Known?mentioning
confidence: 99%
“…All S. mansoni sirtuins have been expressed throughout the parasitic life cycle and characterized (Lancelot et al, 2013). Initial experiments in adult worms and schistosomula have demonstrated strong effects of hSirt2 inhibitors on both life span and reproduction (Lancelot et al, 2013), and Schiedel et al found that the smSirt2 IC50 was less than 50 μM (Schiedel et al, 2015). These results suggest that schistosome sirtuins could be potential therapeutic targets and validate screening for selective sirtuin inhibitors as a strategy for the development of new drugs against schistosomiasis.…”
Section: Drug Targets Of Epigenetic Regulation To Control Schistosomimentioning
confidence: 99%